2012
DOI: 10.1007/s00520-012-1565-x
|View full text |Cite
|
Sign up to set email alerts
|

Male coping processes as demonstrated in the context of a cancer-related social support group

Abstract: The findings of this study can contribute to the development of interventions aimed at increasing the effectiveness of male coping in group-focused supportive services in cancer care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 41 publications
0
38
0
2
Order By: Relevance
“…[99][100][101][102][103][134][135][136][207][208][209][210][211][212][213][214][215][216][217][218] Three studies were reported across multiple papers that were individually eligible for inclusion. [118][119][120][121][124][125][126] An additional two papers that did not meet the eligibility criteria as they had female-only samples are included in the synthesis because they presented data about women that formed the basis of gender comparisons made by the authors of included studies reporting findings from male participants.…”
Section: General Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…[99][100][101][102][103][134][135][136][207][208][209][210][211][212][213][214][215][216][217][218] Three studies were reported across multiple papers that were individually eligible for inclusion. [118][119][120][121][124][125][126] An additional two papers that did not meet the eligibility criteria as they had female-only samples are included in the synthesis because they presented data about women that formed the basis of gender comparisons made by the authors of included studies reporting findings from male participants.…”
Section: General Study Characteristicsmentioning
confidence: 99%
“…The majority of the studies were conducted in the USA (n = 13 studies) 101,110,113,114,123,[128][129][130]136,208,213,217 and the UK (n = 11), 99,100,102,108,112,115,116,128,209,214,216 with the remainder in Australia (n = 5), 109,111,118,210,212 Canada (n = 5) 107,117,120,125,211 and the following: Denmark, 207 France, 218 South Africa 215 and Sweden…”
Section: Countrymentioning
confidence: 99%
See 3 more Smart Citations